View Transformation Based on a Single Outdoor Image. (3rd May 2013) - Zhang, Shi-Hui; Yan, Shuo
Abstract An automatic approach for view transformation based on a single outdoor image is proposed in this paper. First, the hierarchical segmentation method is conducted to segment an outdoor image into several meaningful regions and each region is labelled as sky, ground or standing object. Then, different methods are used to estimate each region's depth according to its label. After that, the obtained depth information is utilized to create a new view image after any rotation, translation and pitch. Finally, the image inpainting work for the missing colour region is accomplished using its neighbour's colour. Extensive experiments show the proposed approach not only improves the accuracy of view transformation, but also performs well even for images with occlusion phenomena.